Are more resources always better for growth? Resource stickiness in market and product expansion - Mishina, Yuri; Pollock, Timothy G.; Porac, Joseph F. (Strategic Management Journal, 2004)
Abstract We examine how managerial growth logics combine with financial and human resource slack to influence the short‐term revenue growth of a sample of 112 manufacturing firms drawn from a unique database provided by the Ewing Marion Kauffman Foundation. Our results provide evidence that firms pursuing product expansion logics generally grow more slowly than firms that are not expanding their product base, but that financial slack positively moderates this relationship. We also find that human resource slack enhances short‐term market expansion, but slows down short‐term product expansion. We discuss the implications of these results for resource‐based views of growth. Copyright © 2004 John Wiley & Sons, Ltd.